2021
DOI: 10.3390/ijms22041714
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Potential of a-Azepano- and 3-Amino-3,4-SeCo-Triterpenoids

Abstract: Semi-synthetic triterpenoids, holding an amino substituted seven-membered A-ring (azepano-ring), which could be synthesized from triterpenic oximes through a Beckmann type rearrangement followed by a reduction of lactame fragment, are considered to be novel promising agents exhibiting anti-microbial, alpha-glucosidase, and butyrylcholinesterase inhibitory activities. In this study, in an attempt to develop new antitumor candidates, a series of A-ring azepano- and 3-amino-3,4-seco-derivatives of betulin, oleano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Recently we have found that modification of triterpenoids to indole derivatives on the A-ring with amidation to C28-amide, as well as the introduction of piperazine or N -methyl-piperazine, have a positive effect on anticancer activity [ 32 , 33 ]. Chalcone derivatives of messagenine and platanic acid [ 25 ], polyamino-lupanes [ 34 ], A-azepano-, and 3-amino-3,4-seco-triterpenoids [ 35 ] were also found to be effective antiproliferative agents against different cancer cell lines with submicromolar concentration values of GI 50 < 1 μM.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have found that modification of triterpenoids to indole derivatives on the A-ring with amidation to C28-amide, as well as the introduction of piperazine or N -methyl-piperazine, have a positive effect on anticancer activity [ 32 , 33 ]. Chalcone derivatives of messagenine and platanic acid [ 25 ], polyamino-lupanes [ 34 ], A-azepano-, and 3-amino-3,4-seco-triterpenoids [ 35 ] were also found to be effective antiproliferative agents against different cancer cell lines with submicromolar concentration values of GI 50 < 1 μM.…”
Section: Introductionmentioning
confidence: 99%
“…Natural terpenoids and their synthetic analogs are a promising source of new drugs for treating various diseases. These compounds are characterized by a massive variety of molecular structures, low toxicity, and the ability to affect several specific targets inside cells, which determines a wide range of their biological activity, including anti-inflammatory, antitumor, and antiviral properties ( Paduch and Kandefer-Szerszen, 2014 , Rodriguez-Rodriguez, 2015 , Kazakova et al, 2021 , Chen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The different biological activities of pentacyclic triterpenoids may be due to the presence of following functional groups: ketone, ester, amino, oxime, sulfonate, and alkyne attached to the lupane skeleton. Unfortunately, the use of betulin as a potential therapeutic substance is limited by its poor solubility in water and low bioavailability [1,[3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%